Kepemimpinan Instruksional Kepala Sekolah di SMP Muhammadiyah 48 Medan - Intan Ramadani; Inom Nasution; Zulkifli Tanjung (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study was conducted to determine the principal's strategy in implementing instructional leadership at SMP Muhammadiyah 48 Medan. The steps implemented by the principal of SMP Muhammadiyah 48 Medan in developing instructional leadership at SMP Muhammadiyah 48 Medan. The methodology of this study uses a qualitative research approach with a case study research type. In this study, data collection was carried out using several techniques, namely, interviews, observations, and documentation. The subjects of this study include the principal as the main informant along with the vice principal, teachers, as supporting informants. The analysis of this research data through steps including data collection, data reduction, data presentation, and drawing conclusions/verification. The results of this study indicate that the principal's strategy in implementing instructional leadership at SMP Muhammadiyah 48 Medan consists of: The strategy carried out by the principal in implementing instructional leadership is good, but still requires development to implement instructional leadership in schools. So that the implementation of this leadership is worthy of being developed and can be an example for other schools. The steps implemented by the principal related to instructional leadership are very good, because the principal covers the whole leadership from teachers, staff and students in the school. The role played by the principal is quite good, because the principal carries out the role of instructional leadership to understand that one of their tasks is to encourage teachers and other school members to join in their efforts and focus their energy on school goals.